Gambaran Kadar Glukosa Darah Puasa pada Pasien Stroke Iskemik di RSUP Prof. Dr. R. D. Kandou Manado Tahun 2022 - Teofaniblesstin Mangontan; Siemona L. Berhimpon; Mayer F. Wowor (Medical Scope Journal, 2024)
Abstract: Ischemic stroke is the most common type of strokes, especially in patients with history of diabetes—a non-modifiable risk factor. Hyperglycemia is common in acute ischemic stroke patients, whether with or without history of diabetes. This study aimed to obtain the overview of fasting blood glucose (FBG) levels in ischemic stroke patients at Prof. Dr. R. D. Kandou Hospital in 2022. This was a retrospective and descriptive study using secondary data from medical records of ischemic stroke patients at Prof. Dr. R. D. Kandou in 2022 using total sampling method. The results showed that of 40 samples, the predominance were female patients (55.0%) with FBG levels of ≥126 mg/dL (27.5%), aged 56–65 years (35.0%) with FBG levels of ≥126 mg/dL (12.5%), without history of diabetes (70.0%) with FBG levels of 70–99 mg/dL (30.0%), and stroke in the acute phase (90.0%) with FBG levels of 70–99 mg/dL (32.5%). In conclusion, ischemic stroke patients were predominantly female and aged 56–65 years with hyperglycemic FBG levels. Additionally, most patients had no history of diabetes and were in the acute phase with normal FBG levels. Keywords: fasting blood glucose; ischemic stroke; diabetes mellitus    Abstrak: Stroke iskemik merupakan jenis stroke yang paling sering ditemukan, terutama pada pasien dengan riwayat diabetes. Diabetes merupakan faktor risiko stroke yang tidak dapat diubah. Keadaan hiperglikemia umum ditemukan pada pasien stroke iskemik akut, baik dengan atau tanpa riwayat diabetes. Penelitian ini bertujuan untuk mengetahui gambaran kadar glukosa darah puasa (GDP) pada pasien stroke iskemik di RSUP Prof. Dr. R. D. Kandou Manado tahun 2022. Penelitian ini bersifat deskriptif retrospektif menggunakan data sekunder rekam medis pasien stroke iskemik di RSUP Prof. Dr. R. D. Kandou tahun 2022 diperoleh dengan metode total sampling. Hasil penelitian mendapatkan 40 sampel pasien dengan stroke iskemik yang didominasi oleh jenis kelamin perempuan (55,0%) dengan kadar GDP ≥126 mg/dL (27,5%), usia 56–65 tahun (35,0%) dengan kadar GDP ≥126 mg/dL (12,5%), tanpa riwayat diabetes melitus (70,0%) dengan kadar GDP 70–99 mg/dL (30,0%), dan stroke fase akut (90,0%) dengan kadar GDP 70–99 mg/dL (32,5%). Simpulan penelitian ini ialah pasien stroke iskemik di RSUP Prof. Dr. R. D. Kandou Manado tahun 2022 didominasi oleh perempuan dan kelompok usia 56–65 tahun dengan kadar GDP hiperglikemia, serta tanpa riwayat diabetes melitus dan fase akut dengan kadar GDP normal. Kata kunci: glukosa darah puasa; stroke iskemik; diabetes melitus